PENGARUH TEKNIK RELAKSASI BENSON TERHADAP PENURUNAN SKALA NYERI POST APPENDIXTOMY DI RSU D PORSEA - Manurung, Melva (Universitas Prima Indonesia, 2019)
Benson relaxation is the development of a respiratory relaxation response method involving patient confidence factors that can create an internal environment so as to help patients achieve health and wellbeing conditions. The purpose of this study was to analyze the Effect of Benson Relaxation Technique on the decrease of Post Appendixtomy pain scale at Porsea Hospital Year 2019. The research design used was quasi experimental research with a static group comparison design (posttest only control group design). The population of stroke patients in Porsea Hospital with a sample of 18 respondents. The gauge uses a research guide for Benson Relaxation on the post-Appendixtomy pain scale reduction at Porsea Hospital. Data were analyzed by t test. The result of t test analysis of control group pre experiment and pre experiment group of intervention obtained value p = 0.003, there is difference of decrease of pain scale post Appendixtomy after Benson relaxation. The result of t-test post experiment of control group and post experiment of intervention group obtained p value = 0.000, there is difference of difference of decrease of pain scale post Appendixtomy after Benson relaxation. Benson relaxation is one way to reduce pain by involving patient confidence factors that can create an internal environment so as to help patients achieve health and wellbeing conditions. Nurses in the role of nursing careers especially in decreasing the scale of pain, more sensitive to special populations ie individuals with various diseases that cause pain